{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

FA06Ma.Hw8solutions

# FA06Ma.Hw8solutions - 5 5.10.14(p221 Use integration by...

This preview shows pages 1–2. Sign up to view the full content.

Math 1a, Section 1 Solutions to Homework 8 1. Q1 - See solutions in the book. 2. Q2 - See solutions in the book. 3. 5.8.3, 5.8.14, 5.8.18 (p216) (a) Let y = 1 + x . Then x 2 = ( y - 1) 2 and dx = dy . Hence, Z x 2 1 + xdx = Z ( y - 1) 2 ydy = y 7 / 2 / (7 / 2) - 2 y 5 / 2 / (5 / 2) + y 3 / 2 / (3 / 2) = (1 + x ) 7 / 2 / (7 / 2) - 2(1 + x ) 5 / 2 / (5 / 2) + (1 + x ) 3 / 2 / (3 / 2) (1) (b) Let y = 1 - x 6 . Then dy/dx = - 6 x 5 . Hence Z x 5 1 - x 6 dx = Z dy - 6 y = - 1 / 3(1 - x 6 ) 1 / 2 (2) (c) Let y = sin x - cos x . Then dy/dx = cos x + sin x . Hence Z sin x + cos x (sin x - cos x ) 1 / 3 dx = Z y - 1 / 3 dy = 3(sin x - cos x ) 2 / 3 2 (3) 4. 5.10.7 (p220) Z sin 2 xdx = Z sin x d ( - cos x ) = - cos x sin x - Z ( - cos x ) d sin x = - cos x sin x + Z cos 2 xdx (4) Apply cos 2 x = 1 - sin 2 x to the right hand side of (4). Then we have 2 Z sin 2 xdx = - sin x cos x + x (5) Furthermore, sin(2 x ) = 2 sin x cos x and the result follows.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 5. 5.10.14 (p221) Use integration by parts to obtain Z √ 1-x 2 dx = x √ 1-x 2-Z xd ( √ 1-x 2 ) = x √ 1-x 2-Z x ±-2 x 2 √ 1-x 2 ² dx = x √ 1-x 2 + Z x 2 dx √ 1-x 2 (6) Since x 2 = x 2-1 + 1, Z x 2 dx √ 1-x 2 = Z x 2-1 √ 1-x 2 + 1 √ 1-x 2 dx =-Z √ 1-x 2 dx + Z 1 √ 1-x 2 dx (7) Substituting (7) into (6), we arrive at the following and the result follows. 2 Z √ 1-x 2 dx = x √ 1-x 2 + Z 1 √ 1-x 2 dx (8)...
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

FA06Ma.Hw8solutions - 5 5.10.14(p221 Use integration by...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online